The Flash Cards for Increase Ability Long Term Memory - Pambudi, Gigih; Adulrahman, Indra Syamsuri; Leksono, Suroso Mukti (Universitas PGRI Sumatera Barat, 2024)
The brain consists of the right and left hemispheres. The brain is divided into three regions, namely: forebrain (frontal), midbrain (parietal), back brain (occipital). The most important process in the brain is during the growth or myelination period. Environment influences brain plasticity. Memory or memories in the brain occur due to changes in synaptic connections, the formation of episodic memory depends on the hippocampus. To store information in long-term memory, the limbic system or mammalian brain, namely the hippocampus, plays a very important role. To be able to develop this process, media is needed to speed it up, one of which is flash cards which have a recall principle. The method used is qualitative with a literature study approach. The results of this study show that there is a relationship between the use of flash cards and the brain's ability to improve long-term memory processing. Apart from that, the results of a literature study found that flash cards have been proven to improve long-term memory abilities and can make learning more enjoyable. In this way, student learning outcomes also increase which can be seen from the percentage of learning outcomes.